Photoluminescence Modulation of Ruddlesden-Popper Perovskite via Phase Distribution Regulation - Xinwei Zhao; Ting Zheng; Weiwei Zhao; Yuanfang Yu; Wenhui Wang; Zhenhua Ni (Nanomaterials, 2023)
The intrinsic chaotic phase distribution in Ruddlesden-Popper Perovskite (RPP) hinders its further improvement of photoluminescence (PL) emission and limits its application in optical devices. In this work, we achieve the phase distribution regulation of RPP by varying the composition ratio of organic bulky spacer cations 1-naphthylmethylamine (NMA) and phenylethyl-ammonium (PEA), which is controllable and nondestructive for structures of RPP. By suppressing the small n-phase, the PL intensity emission of RPP is further improved. Through the time-resolved PL (TRPL) measurements, we find the PL lifetime of the sample with 66% PEA concentration increases with the temperature initially and possesses the highest values of <semantics>τ1</semantics> and <semantics>τ2</semantics> at ~255 K, indicating the immediate state assisting exciton radiative recombination, and it can be modulated by phase manipulation in RPP. The immediate state may outcompete other non-radiative decay channels for excited carriers, leading to the PL enhancement in RPP, and broadening its further application.